2006
DOI: 10.17221/3919-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of performance and digestibility characteristics of broilers fed diets containing treated hulled barley or hulless barley

Abstract: This study was performed with growing chickens (14 to 56 days of age) to evaluate the effects of feeding a barley-based diet. The treatments were maize diet (1) as a control, barley diet with (4) or without (2) the commercial enzyme β-glucanase, barley treated with rumen fluid without protozoa (3) and hulless barley (5). The effects of treatments were investigated in a 42-day trial using 360 sexed broiler chickens. In a digestibility trial, 15 male broiler chicks were used at 45 days of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Conversely, gall bladder relative weight tended to reduce in MCFA treatments. Therefore, MCFAs may have special effects on lipid digestion and absorption and diminishing of energy consumption (Moharrery 2006); further researches are needed in this regard.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Conversely, gall bladder relative weight tended to reduce in MCFA treatments. Therefore, MCFAs may have special effects on lipid digestion and absorption and diminishing of energy consumption (Moharrery 2006); further researches are needed in this regard.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…There was a significant (P<0.05) variation in fat digestibility in all the treatments which was higher in the control and enzyme treated diets compared to diets without enzyme supplementation. Salih et al (1991) and Moharrery, (2006) suggested that the low lipid digestibility in broilers chicken fed diets with a high content of NSPs might be due to bacterial overgrowth in the small intestine and subsequent excessive deconjugation of bile acids, which reduced their efficacy in solubilizing lipids. Sekoni et al (2008) reported an improvement in the body weight and feed conversion efficiency due to an increase in fat digestibility which consequently increased bioavailability of fat soluble vitamins and protein digestibility when enzyme maxigrainÂź was fed to broilers.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Conversely, in the current study, gall bladder weight reduced as a result of drinking water supplementation of LE (0.1 g/L of water). Therefore, LE may have exerted especial effects on lipid digestion and absorption, which could result in reduced energy consumption [30]; further experiments are necessary to confirm this result. Tominaga et al [9] established a hypothesis that the weight loss by LFO is due to reduction in fatty acid synthesis and enhancement of fatty acid oxidation in the liver, and lines of evidence exist confirming this supposition.…”
Section: Discussionmentioning
confidence: 98%